Early Intervention in Neonatal Gastric Volvulus: A Case Report on Prompt Diagnosis and Surgical Success - Purnama Parulian Siahaan; Thomas Aribowo Kristianto (Open Access Indonesian Journal of Medical Reviews, 2025)
Neonatal gastric volvulus (NGV) is an uncommon but potentially life-threatening surgical emergency characterized by the abnormal rotation of the stomach around one of its axes. This condition can lead to gastric outlet obstruction, ischemia, necrosis, and perforation if not promptly diagnosed and managed. The clinical presentation is often nonspecific, posing significant diagnostic challenges. Early recognition and immediate surgical intervention are paramount for favorable outcomes. We report the case of a 7-day-old female neonate who presented with recurrent postprandial, non-bilious vomiting and significant orogastric tube residuals since the first few days of life. Antenatal and perinatal histories were largely unremarkable. Initial physical examination revealed a generally stable neonate with mild distress during vomiting episodes, but the abdomen was soft, non-distended, and without palpable masses or signs of peritonitis. Laboratory investigations were within normal neonatal limits. A plain abdominal radiograph was initially inconclusive but suggested some degree of gastric distension. Subsequent upper gastrointestinal (UGI) contrast study revealed features consistent with organoaxial gastric volvulus, demonstrating abnormal positioning of the greater curvature of the stomach and obstruction to contrast passage. Exploratory laparotomy confirmed organoaxial gastric volvulus secondary to marked laxity of the gastrocolic and gastrosplenic ligaments. Detorsion of the stomach and an anterior gastropexy were performed. Postoperatively, the patient had an uneventful recovery, with gradual introduction and tolerance of oral feeds. Follow-up at 6 months showed normal growth and no recurrence of symptoms. Neonatal gastric volvulus remains a diagnostic challenge due to its rarity and nonspecific symptoms. A high index of suspicion, particularly in neonates with persistent, non-bilious vomiting, is crucial. Prompt radiological evaluation, typically with an UGI series, can confirm the diagnosis. Early surgical intervention involving detorsion and gastropexy is the mainstay of treatment and is associated with excellent outcomes, preventing potentially lethal complications. This case underscores the importance of early diagnosis and timely surgical management in achieving successful outcomes in neonatal gastric volvulus.